Nitrate and ammonium proportions in sesame cultivation under irrigation with saline waters - Lima, Geovani Soares de; Dias, Adaan Sudario; Gheyi, Hans Raj; Soares, Lauriane Almeida dos Anjos; Nobre, Reginaldo Gomes; Silva, Francisco de Assis França Dantas da (Comunicata Scientiae, 2019)
This research was conducted with the aim of evaluating the water relations, growth and the production components of the sesame cv. CNPA G3, in function of the irrigation with waters of different salinities and fertilization with different proportions of nitrate (N-NO3-) and ammonium (N-NH4+). The study was performed in drainage lysimeters in conditions of greenhouse, in the municipality of Campina Grande, PB, Brazil. The adopted design was in randomized blocks, in a factorial scheme of 5x5 with three repetitions, whose treatments were constituted of five levels of electrical conductivity of the irrigation water - ECw (0.6; 1.2; 1.8; 2.4 and 3.0 dS m-1) and five proportions of nitrate and ammonium (200:0; 150:50; 100:100; 50:150; 0:200 mg kg-1 of soil). The irrigation with ECw superior to 0.6 dS m-1 negatively affected the growth and production of the sesame; the fertilization with N-NH4+ and N-NO3- in the proportion 200:0 resulted in a higher percentage of cell membrane damage; the utilization of N-NH4+ and N-NO3- in the proportion 50:150 provided increase in the relative water content in the leaf blade and in the mass of a hundred seeds; N-NO3 and N-NH4+ proportions of 200:0 and 150:50 and water with ECw of 0.6 dS m-1 promoted the highest values for the content of chlorophyll a and total number of sesame seeds.